Aerobic and Anaerobic Microbiology of Surgical-Site Infection Following Spinal Fusion - Brook, Itzhak (American Society for Microbiology, 1999)
The aerobic and anaerobic microbiology of surgical-site infections (SSI) following spinal fusion was retrospectively studied. This was done by reviewing the clinical and microbiological records at the Naval Hospital in Bethesda, Md., from 1980 to 1992. Aspirates of pus from 25 infection sites showed bacterial growth. Aerobic bacteria only were recovered from 9 (36%) specimens, anaerobic bacteria only were recovered from 4 (16%), and mixed aerobic and anaerobic bacteria were recovered from 12 (48%). Sixty isolates were recovered: 38 aerobes (1.5 isolates per specimen) and 22 anaerobes (0.9 isolate per specimen). The predominant aerobes were Escherichia coli (n = 8) and Proteus sp. (n = 7). The predominant anaerobes were Bacteroides fragilis group (n = 9) and Peptostreptococcus sp. (n = 6) isolates. An increase in recovery of E. coli and B. fragilis was noted in patients with bowel or bladder incontinence. This study highlights the polymicrobial nature of SSI and the importance of anaerobic bacteria in SSI following spinal fusion.